PETUALANGAN INSPIRATIF BERBASIS ANDROID MEMPERKENALKAN FIGUR PAHLAWAN PAPUA KEPADA GENERASI DIGITAL DI KEPULAUAN RAJA AMPAT: INSPIRATIONAL ANDROID-BASED ADVENTURE INTRODUCES PAPUAN HEROES TO THE DIGITAL GENERATION IN THE RAJA AMPAT ISLANDS - Fitriyani Tella; Virasanty Muslimah; Agniel Lorensyus Malino; Ridho Bintang Ramadhan (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Papua has a number of national heroes who have made significant contributions to the integration of the Papua region into the Unitary State of the Republic of Indonesia (NKRI). Although their role is very important in the history of the nation, there are still many young people, especially in the Papua region, who do not know or understand the values of these figures' struggles. Therefore, innovative learning media is needed to convey history in an interesting and interactive way. The development of an Android-based educational game with the theme of Papuan heroes' adventures. The purpose of this research is to design an Android-based adventure game to introduce Papuan heroes to the digital generation and to implement an Android-based adventure game about Papuan heroes for the younger generation in the Raja Ampat Islands. The research method used the Game Development Life Cycle (GDLC) approach with the stages of Initiation, Pre-production, Production, Alpha Testing, Beta Testing, and Release. The application development process was carried out using Unity software, while system testing was conducted through blackbox testing to ensure that all functions and interfaces in the game worked properly. In addition, usability testing was also conducted to assess the level of feasibility and comfort of users in playing the game. The test results showed that all functions worked very well without any bugs. Meanwhile, the usability score of 94% indicated that the game was highly feasible and had the potential to be an effective educational medium.